The impact of climate change on African economies and opportunities for agrifood system transformation - Tankari, Mahamadou; Fofana, Ismael (AKADEMIYA2063, 2024)
As in the rest of the world, the climate is changing in Africa, with data showing a slightly faster warming trend than the global average of around +0.2°C per decade for the 1991–2022 period. In Africa, the average rate of change of temperature was around +0.3°C per decade between 1991 and 2022, while it was estimated at +0.2°C per decade between 1961 and 1990. In addition, all six African subregions have experienced an increase in warming over the past 60 years compared with the period before 1960. Due to global warming, Africa is observing a change in precipitation patterns, a rise in sea level, and an increase in the frequency and intensity of extreme weather events such as droughts, floods, extreme heat, and cyclones (WMO 2023). For instance, the report on the State of the Climate in Africa in 2022 (WMO 2023) showed that precipitation anomalies were above the 1991–2020 average in northeastern Africa, large parts of West Africa, the eastern Sahel region, Sudan, and parts of South Africa. In addition, several regions experienced rainfall deficits including the western part of North Africa, the Horn of Africa, portions of southern Africa, and Madagascar. Sea level rise in Africa’s seven coastal regions has been similar to the global sea level average rate of increase of 3.4 millimeters (plus or minus 0.3 millimeters) per year between 1990 and 2020. In addition, extreme weather events are growing in frequency and intensity. With respect to extreme weather events including droughts, floods, extreme heat, and cyclones, data from the Emergency Event Database in Africa showed that 80 meteorological, hydrological, and climate-related hazards were reported in 2022 (WMO 2023).